Revealing Shared and Distinct Gene Network Organization in Arabidopsis Immune Responses by Integrative Analysis. Issue 3 (22nd January 2015) - Dong, Xiaobao; Jiang, Zhenhong; Peng, You-Liang; Zhang, Ziding
Abstract : Multiscale network analysis shows a robust gene network architecture in effector-triggered immunity of Arabidopsis. Abstract: Pattern-triggered immunity (PTI ) and effector-triggered immunity (ETI ) are two main plant immune responses to counter pathogen invasion. Genome-wide gene network organizing principles leading to quantitative differences between PTI and ETI have remained elusive. We combined an advanced machine learning method and modular network analysis to systematically characterize the organizing principles of Arabidopsis ( Arabidopsis thaliana ) PTI and ETI at three network resolutions. At the single network node/edge level, we ranked genes and gene interactions based on their ability to distinguish immune response from normal growth and successfully identified many immune-related genes associated with PTI and ETI . Topological analysis revealed that the top-ranked gene interactions tend to link network modules. At the subnetwork level, we identified a subnetwork shared by PTI and ETI encompassing 1, 159 genes and 1, 289 interactions. This subnetwork is enriched in interactions linking network modules and is also a hotspot of attack by pathogen effectors. The subnetwork likely represents a core component in the coordination of multiple biological processes to favor defense over development. Finally, we constructed modular network models for PTI and ETI to explain the quantitative differences in the global network architecture. Our results indicate that the defense modules in ETI are organized into relatively independent structures, explaining the robustness of ETI to genetic mutations and effector attacks. Taken together, the multiscale comparisons of PTI and ETI provide a systems biology perspective on plant immunity and emphasize coordination among network modules to establish a robust immune response.